The Influence of Product Quality, Promotion and Role of Influencers on Customer Trust and Their Implications in Financing Decisions at KPR Bank XYZ Syariah - Darifah, Darifah; Erna Sofriana Imaningsih; Dudi Permana (Dinasti International Journal of Digital Business Management, 2023)
This study aims to analyze the role of Trust as a mediator between the relationship between product quality, promotion and the role of influencer on mortgage financing decisions at Bank XYZ Syariah. This research was conducted using a quantitative method with a total sample of 370 respondents who were customers of Bank XYZ Syariah using a purposive sampling technique. Researchers used a questionnaire to collect data. The data analysis technique used in this study was The Structural Equation Modeling (SEM) from the PLS 3.0 statistical software package. Based on the results of the study, it was found that product quality did not directly influence financing decisions, promotion had a direct effect on financing decisions, the role of influencer had a direct effect on financing decisions, trust was proven to be able to mediate the relationship between product quality, promotion and the role of influencer on financing decisions, and Trust able to perfectly mediate the relationship between product quality and financing decisions.